2015
DOI: 10.1096/fj.15-272302
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor for advanced glycation end products inhibits disease progression in autosomal dominant polycystic kidney disease by down-regulating cell proliferation

Abstract: Autosomal polycystic kidney disease (ADPKD) is a highly prevalent genetic renal disorder in which epithelial-lining fluid-filled cysts appear in kidneys. It is accompanied by hyperactivation of cell proliferation, interstitial inflammation, and fibrosis around the cyst lining cells, finally reaching end-stage renal disease. Previously, we found high expression of ligands stimulating the receptor for advanced glycation end products (RAGE) in ADPKD mice. Furthermore, gene silencing of RAGE was revealed to cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In the present study, TNF-α, IL-6, and CRP levels were significantly higher in the PCOS group compared to the control group, and these results support the findings from many other studies [31,32]. sRAGE inhibits the effect of RAGE, which can inhibit the expression of inflammatory cells and inhibit the inflammatory reaction mediated by an injury [16,33]. Romero et al believed that patients with preterm labor have increased amniotic fluid concentrations of sRAGE, and these levels are positively associated with intraamniotic infection and inflammation [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, TNF-α, IL-6, and CRP levels were significantly higher in the PCOS group compared to the control group, and these results support the findings from many other studies [31,32]. sRAGE inhibits the effect of RAGE, which can inhibit the expression of inflammatory cells and inhibit the inflammatory reaction mediated by an injury [16,33]. Romero et al believed that patients with preterm labor have increased amniotic fluid concentrations of sRAGE, and these levels are positively associated with intraamniotic infection and inflammation [9].…”
Section: Discussionsupporting
confidence: 92%
“…We excluded women with diabetes, chronic kidney disease, and complications, such as chronic metabolic diseases and endometriosis [13][14][15][16]. The cycle determinants included age, FSH/LH, body mass index (BMI), total gonadotropin (Gn) dose in international units used per cycle, the number of days of stimulation, the number of oocytes retrieved, the rate of high-quality embryos, and the normal fertilization rate.…”
Section: Subjectsmentioning
confidence: 99%
“…We next assessed Six2creFrs2αKO mice for increased epithelial cell proliferation, apoptosis, and interstitial fibrosis, other prominent features in PKD153637383940. Co-staining of kidney sections with LTL, and the proliferation marker, Ki67, revealed increases in mutant proximal tubular cell proliferation rates at both P7 and P21 versus controls (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, increased sRAGE levels and decreased HMGB1 levels were observed in patients with GBS after treatment, while sRAGE levels and HMGB1 levels appear to be normal in plateau phase. This question strongly warrants further inquiry, as recent studies have reported that administration of recombinant sRAGE or anti-HMGB1 monoclonal antibodies have therapeutic benefit for several diseases, including acute ischemic stroke for both therapies, autosomal dominant polycystic kidney disease in the case of recombinant RAGE, and sepsis and autoimmune myocarditis in the case of HMGB1 monoclonal antibody therapy 39 40 . Several studies have demonstrated that administration of recombinant sRAGE effectively protects brain tissues in a mouse model of stoke from injury and primary neurons in culture from cell death via a mechanism involving reduced activation of c-Jun amino-terminal kinase and NF-κB 39 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that administration of recombinant sRAGE effectively protects brain tissues in a mouse model of stoke from injury and primary neurons in culture from cell death via a mechanism involving reduced activation of c-Jun amino-terminal kinase and NF-κB 39 41 . Administration of recombinant sRAGE in a mouse model of autosomal dominant polycystic kidney disease reduces cysts and promotes enhanced renal function, inhibition of cell proliferation, inflammation, and fibrosis 40 . Similarly, anti-HMGB1 monoclonal antibody intervention has been reported to reduce IL-6 and TNF-α release from macrophage-like cells, to attenuate lethality in an established sepsis 42 .…”
Section: Discussionmentioning
confidence: 99%